Genome-wide DNA methylation analysis of the porcine hypothalamus-pituitary-ovary axis - Xiao-Long Yuan (Nature Portfolio, 2017)
Abstract Previous studies have suggested that DNA methylation in both CpG and CpH (where H = C, T or A) contexts plays a critical role in biological functions of different tissues. However, the genome-wide DNA methylation patterns of porcine hypothalamus-pituitary-ovary (HPO) tissues remain virtually unexplored. In this study, methylomes of HPO tissues were profiled to investigate their differences and similarities. We found that HPO methylomes displayed tissue-specific methylation patterns in both CpG and CpH contexts. At gene locations, the methylation and density of CpGs was negatively linked at transcription start sites but positively linked at transcription end sites. The densities of CpGs and CpHs at CpG island (CGI) locations were negatively correlated with their methylation. Moreover, the methylation interactions between CGIs and genes showed similar pattern in the CpG context but tissue-specific pattern in the CpH context. CpGs located in CGIs, upstream regions and exons were protected from methylation dynamics, whereas CGI shores, CGI shelves and intergenic regions were more likely to be targets of methylation changes. The methylation dynamics enriching in a tissue-specific manner appeared to maintain and establish the biological functions of HPO tissues. Our analyses provided valuable insights into the tissue-specific methylomes of porcine HPO tissues.